Oral candidiasis - Samaranayake, Lakshman P. (Henry Stewart Talks, 2017)
Historical aspects, Nomenclature and Prevalence, Virulence factors of Candida species, Classification of oral candidiasis, Clinical features and management principles of primary Candida infections, Candida associated lesions, Diagnostic and laboratory aspects